Doctoral training in Physical Education at the Colombian Politecnico Jaime Isaza Cadavid: a look guarantor knowledge networks. (2022)
This article is related to postgraduate training for university teachers from knowledge networks, specifically in the field of knowledge of physical education. The interest of this investigation focused on recognizing the perceptions of directors of Academic Networks of the University of Murcia and the University of Jaén with their doctorate in physical activity and sports sciences. For this, the conceptual reference addressed the categories of knowledge networks and training dynamics for university teaching in physical education. The qualitative research method used was the simple cross-sectional case study, where techniques such as interview and documentary review were applied. The main findings are that doctoral training through cooperative network processes is an innovation in higher education, it is a strategy for the qualification of the professional role of university professors and it is a reflection of contemporary education in the international scenario, while, in In the institutional context, there is still no postgraduate training leading to a doctorate degree and there are no agreements or networks of its own to facilitate such action.